Rancang Bangun Augmented Reality Book Edukasi ‘Klorofil sebagai Penyebab Warna pada Daun’ - Ivani Adellia Talitha; Chintiya Larashati (MASALIQ, 2026)
The limitations of static learning media still make it difficult for elementary school students to understand the concept of chlorophyll and the process of light interaction that causes leaves to appear green. This study aimed to design and develop an educational Augmented Reality Book entitled “Klorofil sebagai Penyebab Warna pada Daun,” which integrates an illustrated book, three-dimensional animation, and a marker-based tracking system. The study employed a research and development approach using the Multimedia Development Life Cycle model, which includes the concept, design, material collecting, assembly, and testing stages. Initial data were obtained through a questionnaire administered to 30 respondents selected using a purposive sampling technique, as well as a literature review. The data were analyzed descriptively through frequencies, percentages, and the categorization of open-ended responses. The results of the study produced an illustrated book consisting of five spreads, low-poly-style three-dimensional models, and an Android-based application developed using Unity and Vuforia. The testing results showed that the augmented reality camera function, marker detection, the appearance of three-dimensional objects, animation, and the exit button operated according to the design. These findings indicate that the integration of print media and augmented reality technology can support the visualization of scientific concepts in a more interactive manner. This study contributes to the development of science learning media that connect printed narratives with digital scientific visualization. Further testing with fifth-grade students is needed to assess the effect of the media on understanding, interest, and learning outcomes.